2006
DOI: 10.3758/bf03192783
|View full text |Cite
|
Sign up to set email alerts
|

Using self-reported data to assess the validity of driving simulation data

Abstract: In this article, we use self-reported driving behaviors from a written questionnaire to assess the measurement validity of data derived from a driving simulation. The issue of validity concerns the extent to which measures from the experimental context map onto constructs of interest. Following a description of the experimental methods and setting, an argument for the face validity of the data is advanced. Convergent validity was assessed by regressing behaviors observed in the driving simulator on self-report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 42 publications
2
53
0
1
Order By: Relevance
“…Furthermore, the classification between safe drivers (without crashes) and unsafe drivers (with crashes in the preceding two years) is based on self-reports alone, a method which is supported by some studies (Lee et al, 2003;Reimer et al, 2006) but challenged by others (Wåhlberg, 2003). Research supports the construct validity of self-reported crash-involvement as proxy measure for driving performance (Lee et al, 2003;Reimer et al, 2006) but part of the criticism is about the duration of time period under consideration, the negligence of culpability, and the retrospective assessment of driving behavior (Wåhlberg, 2003). To overcome the part of the criticism, we followed the suggestions by Wåhlberg (2003), and considered only the preceding two years of driving and crashes, in which participants considered themselves at least partly at fault.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the classification between safe drivers (without crashes) and unsafe drivers (with crashes in the preceding two years) is based on self-reports alone, a method which is supported by some studies (Lee et al, 2003;Reimer et al, 2006) but challenged by others (Wåhlberg, 2003). Research supports the construct validity of self-reported crash-involvement as proxy measure for driving performance (Lee et al, 2003;Reimer et al, 2006) but part of the criticism is about the duration of time period under consideration, the negligence of culpability, and the retrospective assessment of driving behavior (Wåhlberg, 2003). To overcome the part of the criticism, we followed the suggestions by Wåhlberg (2003), and considered only the preceding two years of driving and crashes, in which participants considered themselves at least partly at fault.…”
Section: Discussionmentioning
confidence: 99%
“…One of the issues that researchers are concerned with when using driving simulators is the fact the drivers' behaviour will not be the same under simulated driving since there is not any risk involved (Reimer et al, 2006).…”
Section: Driving Simulatorsmentioning
confidence: 99%
“…They also concluded that, although participants generally drove faster in real life than in the driving simulator, the driving simulator possesses relative validity. Finally, Reimer et al (2006) conducted a validation study on driving simulators using self-reports. Significant relationships were found with regard to accidents, speeding, velocity, overtaking and behaviour at traffic signs.…”
Section: (B) Driving-simulator Datamentioning
confidence: 99%